Influence of the Effectiveness of Literacy Habits to Improve the Pronunciation of Greetings and Dialog in English Communication in the Elementary School - Ardian Syaputra; Zuhri Efendi (Institut Agama Islam Negeri Palopo, 2024)
Reading is an early activity in the learning process for every student in elementary school. At the beginning of reading, then someone will see how the problems are faced so that it can be considered as a challenge that must be faced. The benefit of reading is that it can develop more significant thoughts that refer to critical thinking, increase knowledge, and provide arguments to each other. This can improve relationships between people through peer communication, to build this literacy culture requires a person to change. Using communication, a person will find it easier to gain knowledge. Communication does not mean just talking but talking about the ability to foster interest in reading and writing. What can result from this culture is that it can foster interest in reading and build reading activities. By reading we can find out new things that we get. Building a culture of literacy can be done anywhere, one of which is by utilizing the school library and applying it in everyday life.